Comparison of the effects of polynucleotide and hyaluronic acid fillers on periocular rejuvenation: a randomized, double-blind, split-face trial. (2nd January 2022) - Lee, Ye Jin; Kim, Hak Tae; Lee, You Jin; Paik, Seung Hwan; Moon, Young Seon; Lee, Woo Jin; Chang, Sung Eun; Lee, Mi Woo; Choi, Jee Ho; Jung, Joon Min; Won, Chong Hyun
Abstract: Background: Filler injection has become an extremely popular method for facial skin rejuvenation, including the periorbital area. In the recent years, new polynucleotide (PN)-containing filler products have been used for esthetic purposes. Aim: We aimed to investigate the efficacy and safety of PN filler injection in the periorbital area. Patients/methods: A total of 27 subjects were enrolled in this randomized, pair-matched, and active-controlled study. Each subject received filler injections thrice with two-week intervals, with a PN filler injection on one side and a non-crosslinked hyaluronic acid (HA) filler injection on the contralateral side of the periorbital area. Results: Improvements in the visual analog scale and global esthetic improvement scale scores were not significantly different between the PN and HA groups. The improvement rates of skin elasticity and hydration decreased over time in both groups, with the PN group showing a higher improvement rate. The improvement rates of roughness and pore volume were higher in the PN group than in the HA group. The improvement rate of dermal density was not significantly different between the groups. No serious adverse events were reported. Conclusion: The PN filler injection is effective and safe for periorbital rejuvenation.